Role of Sodium Channel on Cardiac Action Potential - Sabzpoushan, S. H.; Faghani Ghodrat, A. (Engineering, Technology & Applied Science Research, 2012)
Sudden cardiac death is a major cause of death worldwide. In most cases, it’s caused by abnormal action potential propagation that leads to cardiac arrhythmia. The aim of this article is to study the abnormal action potential propagation through sodium ion concentration variations. We use a new electrophysiological model that is both detailed and computationally efficient. This efficient model is based on the partial differential equation method. The central finite difference method is used for numerical solving of the two-dimensional (2D) wave propagation equation. Simulations are implemented in two stages, as a single cardiac cell and as a two-dimensional grid of cells. In both stages, the normal action potential formation in case of a single cell and it’s normal propagation in case of a two-dimensional grid of cells were simulated with nominal sodium ion conductance. Then, the effect of sodium ion concentration on the action potential signal was studied by reducing the sodium ion conductance. It is concluded that reducing the sodium ion conductance, decreases both passing ability and conduction velocity of the action potential wave front.